ANALYSIS OF QUALITY, DEPOSITIONAL ENVIRONMENT, AND EVALUATION OF UNDERGROUND COAL GASIFICATION POTENTIAL, ON BATULICIN, SOUTH KALIMANTAN - Safitri, Dini
Batulicin is located in Tanah Bumbu Regency, South Kalimantan, Indonesia. Batulicin is a part of the Asem-Asem Basin with the Tanjung Formation as a coal bearing formation. This research aims to find out the quality, depositional environment, and Underground Coal Gasification (UCG) potential in Batulicin. Data used in this study is primary data in the form of vitrinite reflectance data and macerals composition data as well as secondary data in the form of outcrop data, the result of proximate quality analysis data, total sulfur data, 21 drillholes, and maceral type data of PSDMBP. The coal quality analysis will use proximate data and vitrinite reflectance data with maceral type data. While the depositional environment analysis will use macerals composition data and sulfur data. For the analysis of Underground coal gasification, an evaluation of the 10 UCG criteria will be conducted. The correlation of drillholes and outcrop data at the research area of 88,8 km2 showed that the research area consisted of three lithological units from oldest to youngest is Serpih Unit including coal seams A, B, C, D, and E, Serpih-Batulanau Unit, Batulanau Unit. These three units are equivalent to the Lower Tanjung Formation. The result of interpretation based on outcrop data in research area, syncline and anticline structures are mapped in the northwest-southeast direction. The result of the coal quality analysis showed that the rank of coal quality in research area is High Volatile B Bituminous – High Volatile A Bituminous with an average calorific value of 13721,18 btu/lb. Analysis of macerals composition in the form of TPI value (1,9-6,9) and GI (3,8-11,8) showed that coal seams in research area were deposited in wet forest swamp with telmatic hydrological regime. Sulfur levels in coal seams A, B, C, D, dan E has low values (0,29-0,42%) indicating that these coal seams are deposited in environment with tidal influence that is upper delta plain. The geological complexity of the Batulicin area is a simple area. The result of the UCG criteria evaluation shows that the D coal seam has the potential for the development of the Underground Coal Gasification. The UCG potential area is divided into Block A and Block B. Block A potential area of 0,06 km2 with an estimated resource of 26.620.385 tons of coal that can generate 199.683.841 MWh of electricity and gas potential of 79.861,2 MNm3 as well as Block B covering an area of 1,02 km2 with an estimated resource of 34.307.539 tons of coal that can generate 257.346.435 MWh of electricity and gas potential of 102.922,6 MNm3.